A Literature Review on the Management of Facilities and Infrastructure in Kindergartens - Rohayati, Rohayati; Reza Edwin Sulistyaningtyas (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
The management of facilities and infrastructure in kindergartens or Taman Kanak-kanak (TK) plays a crucial role in supporting effective learning processes for early childhood. This article aims to present a literature review of several studies discussing the practices of facilities and infrastructure management in kindergartens. Data sources were obtained from ten scientific articles published between 2020 - 2025 and were analyzed using a qualitative approach. The review results indicate that the main aspects of facilities and infrastructure management include planning, procurement, recording, utilization, maintenance, disposal, and supervision. Discrepancies were found in implementation, particularly in inventory documentation and asset disposal procedures. Many institutions still rely on community involvement without standardized systems. These findings highlight the need for collaboration among stakeholders and proper documentation to support optimal management. This study is expected to contribute to improving the quality of early childhood education (ECE) services through better governance of facilities and infrastructure.